2005
DOI: 10.1213/01.ane.0000184196.60838.8d
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Salivary Biomarkers and State-Trait Anxiety Inventory Score Under Mental Arithmetic Stress: A Pilot Study.

Abstract: Measurement of stress hormones is a common objective method for assessment of mental stress. However, the stress of blood sampling alone may also increase stress hormone levels. In the present study, we sampled salivary biomarkers from healthy volunteers under noninvasive conditions and determined their efficacy to assess mental stress. Specifically, we examined the relationship between State Anxiety Inventory score (STAI-s) in subjects exposed to arithmetic stress and salivary chromogranin-A, alpha-amylase, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(160 citation statements)
references
References 22 publications
10
134
0
10
Order By: Relevance
“…Several studies were conducted to evaluate the effect of various stressors, such as process of bloodletting, stressful videos, intellectual computational processes on alpha amylase, and cortisol levels in saliva (15)(16)(17)(18)(19). Nevertheless, few studies have examined the effects of stressful dental procedures on alpha amylase in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to evaluate the effect of various stressors, such as process of bloodletting, stressful videos, intellectual computational processes on alpha amylase, and cortisol levels in saliva (15)(16)(17)(18)(19). Nevertheless, few studies have examined the effects of stressful dental procedures on alpha amylase in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the blood sampling method, it does not provide an additional stress, which could be a confounding factor in stress models (Noto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The production of salivary amylase is controlled by epinephrine secreted from the adrenal medulla, caused by enhanced activity of the sympathetic nervous-adrenomedullary system [10,11]. The sAMY has recently been shown to be a marker of sympathetic system activity [6,7,10,[12][13][14]. When sudden and stressful stimuli are applied to the human body, the sympathetic fi bers trigger the salivary gland, which secretes amylase before the gland responds to norepinephrine from the adrenal medulla; this is thought to be a faster response than the response to norepinephrine, and it usually occurs within minutes [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the effi cacy of assessing psychological stress objectively by monitoring salivary amylase activity (sAMY) [6,7], and an instrument using this method to assess stress with rapidity and low invasiveness has been marketed for practical use [8,9]. Against this background, the objectives of this study were to investigate the differences in sAMY between DS and GA during ESD, to determine the effi cacy of sAMY as a potential index of a patient's stress level during therapeutic endoscopy, and also to elucidate the causes of such stress.…”
Section: Introductionmentioning
confidence: 99%